Biofortification of plants with altered antioxidant content and composition: genetic engineering strategies. Issue 2 (13th September 2012) - Zhu, Changfu; Sanahuja, Georgina; Yuan, Dawei; Farré, Gemma; Arjó, Gemma; Berman, Judit; Zorrilla‐López, Uxue; Banakar, Raviraj; Bai, Chao; Pérez‐Massot, Eduard; Bassie, Ludovic; Capell, Teresa; et al.
Summary Antioxidants are protective molecules that neutralize reactive oxygen species and prevent oxidative damage to cellular components such as membranes, proteins and nucleic acids, therefore reducing the rate of cell death and hence the effects of ageing and ageing‐related diseases. The fortification of food with antioxidants represents an overlap between two diverse environments, namely fortification of staple foods with essential nutrients that happen to have antioxidant properties (e.g. vitamins C and E) and the fortification of luxury foods with health‐promoting but non‐essential antioxidants such as flavonoids as part of the nutraceuticals/functional foods industry. Although processed foods can be artificially fortified with vitamins, minerals and nutraceuticals, a more sustainable approach is to introduce the traits for such health‐promoting compounds at source, an approach known as biofortification. Regardless of the target compound, the same challenges arise when considering the biofortification of plants with antioxidants, that is the need to modulate endogenous metabolic pathways to increase the production of specific antioxidants without affecting plant growth and development and without collateral effects on other metabolic pathways. These challenges become even more intricate as we move from the engineering of individual pathways to several pathways simultaneously. In this review, we consider the state of the art in antioxidant biofortification and discuss the challenges that remain to be overcome in the development of nutritionally complete and health‐promoting functional foods.